The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3389/fpls.2021.647043
|View full text |Cite
|
Sign up to set email alerts
|

Angular Leaf Spot Resistance Loci Associated With Different Plant Growth Stages in Common Bean

Abstract: Angular leaf spot (ALS) is a disease that causes major yield losses in the common bean crop. Studies based on different isolates and populations have already been carried out to elucidate the genetic mechanisms of resistance to ALS. However, understanding of the interaction of this resistance with the reproductive stages of common bean is lacking. The aim of the present study was to identify ALS resistance loci at different plant growth stages (PGS) by association and linkage mapping approaches. An BC2F3 inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 113 publications
(213 reference statements)
0
8
0
Order By: Relevance
“…These vary from the first cultivar carioca released by the Instituto Agronômico—IAC (Campinas, SP, Brazil) in 1971 (i.e., Carioquinha or Carioca comum) to more recent cultivars, such as IPR-Sábia and IAC-1850, released in 2017 and 2019, respectively. The panel was genotyped using the BeadChip Illumina technology by BARCBean6K_3, with 5,398 SNPs [ 68 ], and validated for GWAS by Almeida et al [ 69 ] and successfully used to identify QRL associated with angular leaf spot by Almeida et al [ 70 ]. All the information on the CDP is given in S1 Table of the Supplementary Materials, including the phenotypic and genotypic data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These vary from the first cultivar carioca released by the Instituto Agronômico—IAC (Campinas, SP, Brazil) in 1971 (i.e., Carioquinha or Carioca comum) to more recent cultivars, such as IPR-Sábia and IAC-1850, released in 2017 and 2019, respectively. The panel was genotyped using the BeadChip Illumina technology by BARCBean6K_3, with 5,398 SNPs [ 68 ], and validated for GWAS by Almeida et al [ 69 ] and successfully used to identify QRL associated with angular leaf spot by Almeida et al [ 70 ]. All the information on the CDP is given in S1 Table of the Supplementary Materials, including the phenotypic and genotypic data.…”
Section: Methodsmentioning
confidence: 99%
“…For linkage mapping, the AM genetic map estimated from 1,114 SNPs genotyped by GBS (genotyping by sequencing) in the AM segregating population BC 2 F 3 ({[(♀AND-277 × ♂IAC-Milênio) × IAC-Milênio] × IAC-Milênio}) was used. The AM population was developed and validated for genetic mapping by Almeida et al [ 70 ] and was composed of 91 inter-pool lines selected according to the carioca grain ideotype. All the information on the genotypes of the AM population is presented in S1 Table in the Supplementary Materials, including the phenotypic and genotypic data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brown, is one of the most devastating diseases of beans and can lead to production losses of more than 80% (Nay et al, 2019). Studies on the inheritance of common bean resistance to ALS have identified several resistance loci, of both greater and lesser effects, showing a predominance of quantitative resistance to the disease (Almeida et al, 2021;Bassi et al, 2017;Keller et al, 2015;Oblessuc et al, 2012;Pereira et al, 2015). In a recent study using 144 Brazilian commercial accessions, only 7% showed resistance to ALS in the V3 phenological stage .…”
Section: Introductionmentioning
confidence: 99%
“…To perform QTL mapping, a linkage map previously constructed for a BC 2 F 3 population was used. This map was built using the software OneMap v2.1.3 (Margarido et al., 2007), which was modified to fit the genetic structure of this specific population (de Almeida et al., 2021). In brief, markers were tested for the expected Mendelian frequencies (1/8:7/8), and those exhibiting segregation distortion were excluded.…”
Section: Methodsmentioning
confidence: 99%